2015
DOI: 10.1039/c5py00624d
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of isobutylene catalyzed by EtAlCl2/bis(2-chloroethyl) ether complex in steel vessels

Abstract: When synthesis of highly reactive polyisobutylene (HR PIB) via cationic polymerization of isobutylene (IB) using ethylaluminum dichloride·bis(2-chloroethyl) ether (EADC·CEE) complex were carried out in metal reactors made of 316 stainless steel (SS), PIB olefin with up to 20% lower exo-olefin content were obtained compared to that obtained in glass reactors (up to 90%). In an effort to investigate this reduction in exo-olefin selectivity in SS reactors, we have studied the polymerization of IB using EADC·CEE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Catalytic chain transfer polymerization (CCTP) in nonpolar solvents at moderate temperatures has developed into one of the most adaptable polymerization techniques for the synthesis of highly reactive polyisobutylene (HRPIB) in recent years. Low molecular weight HRPIB ( M n = 500–5000 g/mol) is a valuable precursor in the preparation of motor oil and fuel auxiliaries. Initially, metal halide (AlCl 3 , GaCl 3 , FeCl 3 , etc.) ether complexes (MX n ·ether) were shown to be better catalysts for the synthesis of HRPIB at moderate temperatures compared to traditional catalysts. However, their application in nonpolar solvents is limited because of poor solubility, which affects the polymerization rate. This issue was lately overcome by employing alkylaluminum dichloride ether complexes as hydrocarbon soluble catalysts. We have shown that the ethylaluminum dichloride (EADC)·bis­(2-chloroethyl) ether (CEE) complex is an effective catalyst, which not only polymerizes pure IB feed but also polymerizes mixed C4 olefin feeds at 0–10 °C to yield up to 88% exo-olefin content . In these studies, polymerization conditions and products have been optimized for a batch reactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic chain transfer polymerization (CCTP) in nonpolar solvents at moderate temperatures has developed into one of the most adaptable polymerization techniques for the synthesis of highly reactive polyisobutylene (HRPIB) in recent years. Low molecular weight HRPIB ( M n = 500–5000 g/mol) is a valuable precursor in the preparation of motor oil and fuel auxiliaries. Initially, metal halide (AlCl 3 , GaCl 3 , FeCl 3 , etc.) ether complexes (MX n ·ether) were shown to be better catalysts for the synthesis of HRPIB at moderate temperatures compared to traditional catalysts. However, their application in nonpolar solvents is limited because of poor solubility, which affects the polymerization rate. This issue was lately overcome by employing alkylaluminum dichloride ether complexes as hydrocarbon soluble catalysts. We have shown that the ethylaluminum dichloride (EADC)·bis­(2-chloroethyl) ether (CEE) complex is an effective catalyst, which not only polymerizes pure IB feed but also polymerizes mixed C4 olefin feeds at 0–10 °C to yield up to 88% exo-olefin content . In these studies, polymerization conditions and products have been optimized for a batch reactor.…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing temperature, molecular weights could be increased, , but at the expense of polymerization rate. Decreasing the [CEE]/[EADC] ratios from 1.5 to 1, the molecular weight increases but the exo content drops (from 90 to 70%). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the past few years several new catalyst systems have been developed to synthesize HRPIB. Among the various approaches, high percentage (up to 90%) of exo-olefin content could be achieved in either dehydrochlorination of tert -chlorine-terminated PIB (PIBCl) or quenching the living PIB cations with dialkyl ether/base, dialkyl (or) diaryl sulfide/base, or hindered bases. ,, Solvent-ligated [M­(NCMe) 6 ] 2+ (M II = Mn, Cu, Mo, Fe, or Zn) complexes with weakly coordinating borate or aluminate anions were also established as an effective initiating systems to prepare HRPIB with high exo-olefin functionality . Very recently, Lewis acid (LA) and Lewis base (LB) complexes were reported for the catalytic chain transfer polymerization of IB, and several research groups have made significant contributions to develop effective LA·LB initiating systems to prepare HRPIB. ,,, In our earlier attempts, we developed MCl 3 ·ether complexes (M = Al, Ga, and Fe) to obtain high exo-functionality (up to 85%) at −20 to +10 °C. We also developed an effective co-initiating system by using ethylaluminum dichloride (EADC)·bis­(2-chloroethyl) ether (CEE) complex, which works efficiently in hexanes (nonpolar solvent) at −20 to 20 °C to reach more than 90% exo-olefin content. , …”
Section: Introductionmentioning
confidence: 99%
“…Supporting Information Figure S1 shows a typical 1 H NMR spectrum of a representative HR PIB sample prepared in this study. The M n s ( M n,NMR ) of the HR PIB samples were calculated by the 1 H NMR integrals of end‐groups and backbone‐related peaks of the polymer as described previously …”
Section: Methodsmentioning
confidence: 99%